2002
DOI: 10.1021/ac0203950
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Open-Channel Electroosmotic Pumping System for Microfluidic Sample Handling

Abstract: The development of a novel, fully integrated, miniaturized pumping system for generation of pressure-driven flow in microfluidic platforms is described. The micropump, based on electroosmotic pumping principles, has a multiple open-channel configuration consisting of hundreds of parallel, small-diameter microchannels. Specifically, pumps with microchannels of 1-6 microm in depth, 4-50 mm in length, and an overall area of a few square millimeters, were constructed. Flow rates of 10-400 nL/min were generated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
138
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(140 citation statements)
references
References 47 publications
2
138
0
Order By: Relevance
“…Another important microfluidic structure is the multichannel EOF pump. 4,6,20 This is shown as the upper channel in Fig. 1͑a͒.…”
Section: Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important microfluidic structure is the multichannel EOF pump. 4,6,20 This is shown as the upper channel in Fig. 1͑a͒.…”
Section: Fabricationmentioning
confidence: 99%
“…Microfluidic systems find increasing application in areas such as microelectromechanical systems ͑MEMS͒ sensors [1][2][3] and actuators, [4][5][6] biological analysis, [7][8][9] and microelectronic cooling systems. 10,11 This article considers an electrical-based fluid driving force, electrokinesis ͑also known as electroosmosis͒, that can be applied to these systems.…”
Section: Introductionmentioning
confidence: 99%
“…These pumps can be described as direct open-channel EOF pumps [20][21][22][23][24], which are usually used to perform onchip integratable control of sample reagents in microfluidic chip systems. The open channels in these pumps are usually fabricated with photolithographic microfabrication technologies.…”
Section: Introductionmentioning
confidence: 99%
“…The state of the art of the thermal pump is for interrupted operation rather than continuously pumping. The open-channel electroosmotic pumps (EOPs) are widely used in capillary electrophoresis and in lab-on-a-chip system, and a novel multiple open-channel electroosmotic pumping system for microfluidic sample handling has been reported recently by Lizar and Karger [15]. The disadvantages of the open-channel pump are the unstable flow rate and low pumping output pressure, in most cases lower than 100 cm hydraulic pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Previous study showed that the flow rate of different solvents was not only dependent on the applied voltage and the characteristics of EOP, but also dependent upon the properties of the solvent [9][10][11][12][13][14][15][16]. It had never been approved by experiment about the possible molecular discrimination effect of an EOP for a mixture of organic solvents or a water-organic solvent mixture commonly used in reversed-phase HPLC.…”
Section: Introductionmentioning
confidence: 99%